Poppies of Iraq - Brigitte Findakly (Drawn and Quarterly, 2017)
Signs of an oppressive regime permeate a seemingly normal life: magazines arrive edited by customs; the color red is banned after the execution of General Kassim; Baathist militiamen are publicly hanged and school kids are bussed past them to bear witness. As conditions in Mosul worsen over her childhood, Brigitte's father is always hopeful that life in Iraq will return to being secular and prosperous. The family eventually feels compelled to move to Paris, however, where Brigitte finds herself not quite belonging to either culture. Trondheim brings to life Findakly's memories to create a poignant family portrait that covers loss, tragedy, love, and the loneliness of exile.
Keywords: Autobiography -- Autobiography